Multiplex isolation and profiling of extracellular vesicles using a microfluidic DICE device. Issue 19 (29th August 2019) - Kang, Yoon-Tae; Purcell, Emma; Hadlock, Thomas; Lo, Ting-Wen; Mutukuri, Anusha; Jolly, Shruti; Nagrath, Sunitha
Abstract : We present a simple strategy to immobilize and analyze extracellular vesicles for multiple markers on a microfluidic device, called DICE. Abstract : Profiling of extracellular vesicles (EVs) is an emerging area in the field of liquid biopsies because of their innate significance in diseases and abundant information reflecting disease status. However, unbiased enrichment of EVs and thorough profiling of EVs is challenging. In this paper, we present a simple strategy to immobilize and analyze EVs for multiple markers on a single microfluidic device and perform differentiated immunostaining-based characterization of extracellular vesicles (DICE). This device, composed of four quadrants with a single inlet, captures biotinylated EVs efficiently and facilitates multiplexed immunostaining to profile their extracellular proteins, allowing for a multiplexed approach for non-invasive cancer diagnostics in the future. From controlled sample experiments using cancer cell line derived EVs and specific fluorescence staining with lipophilic dyes, we identified that the DICE device is capable of isolating biotinylated EVs with 84.4% immobilization efficiency. We extended our study to profile EVs of 9 clinical samples from non-small cell lung cancer (NSCLC) patients and healthy donors and found that the DICE device successfully facilitates immunofluorescent staining for both the NSCLC patients and the healthy control. This versatile and simple method to profile EVs could be extended to EVs of any biological origin, promoting discoveries of the role of EVs in disease diagnostics and monitoring.